Aging Analysis of Graphite/LiNi1/3Mn1/3Co1/3O2 Cells Using XRD, PGAA, and AC Impedance. Issue 14 (1st January 2015) - Buchberger, Irmgard; Seidlmayer, Stefan; Pokharel, Aneil; Piana, Michele; Hattendorff, Johannes; Kudejova, Petra; Gilles, Ralph; Gasteiger, Hubert A.
Abstract : The performance degradation of graphite/LiNi1/3 Mn1/3 Co1/3 O2 (NMC) lithium ion cells, charged and discharged up to 300 cycles at different operating conditions of temperature and upper cutoff potential (4.2V/25°C, 4.2V/60°C, 4.6V/25°C) was investigated. A combination of electrochemical methods with X-ray diffraction (XRD) both in situ and ex situ as well as neutron induced Prompt-Gamma-Activation-Analysis (PGAA) allowed us to elucidate the main failure mechanisms of the investigated lithium ion cells. In situ XRD investigations of the NMC material revealed that the first cycle irreversible capacity is the cause of slow lithium diffusion kinetics. In full-cells, however, this "lost" lithium ions can be used to build up the SEI of the graphite electrode during the initial formation cycle. A new systematic approach to correlate the lithium content in NMC with its lattice parameters ( c, a ) allows a convenient quantification of the loss of active lithium in aged cells by determining the c / a ratio of harvested NMC cathodes in the discharged state using ex situ XRD. Besides loss of active lithium, transition metal dissolution/deposition on graphite and growth of cell impedance strongly effect cell aging, especially at elevated temperatures and high upper cutoff potentials.